FAKTOR YANG MEMENGARUHI KEPUASAN KONSUMEN JASA SALON MUSLIMAH DI MASA PANDEMI COVID-19 - Nurzahroh Lailyah; Rozaq Muhammad Yasin; Rhealin Hening Karatri; Dina Lusianti (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The Covid-19 pandemic had decreased number of visitors to Nafisa Salon Muslimah in Semarang. Maintaining customer satisfaction is very important. This study aims to analyze the factors that influence the satisfaction consumers of Nafisa Salon Muslimah services. The sampling technique used was purposive sampling. Data were obtained using a questionnaire distributed to 100 respondents. Consumer data were analyzed using a binary logistic regression model with SPSS software. The results of the study stated that the service, product, price, and maintenance variables affected the satisfaction of the Muslimah Salon consumer service, while the comfort variable was not affected. Therefore, Nafisa Salon Muslimah can provide offline services by implementing strict health protocols and home services, selling care products online through e-commerce during the Covid-19 pandemic.